Histological Markers of Clinical Relapse in Endoscopically Quiescent Ulcerative Colitis. Issue 11 (November 2020) - Kevans, David; Kirsch, Richard; Dargavel, Callum; Kabakchiev, Boyko; Riddell, Robert; Silverberg, Mark S.
Abstract : Background: : In ulcerative colitis (UC) patients who have achieved mucosal healing, active microscopic colonic mucosal inflammation is commonly observed. We aimed to assess the association between histological activity and disease relapse in endoscopically quiescent UC. Methods: : Ulcerative colitis patients with endoscopically quiescent disease and ≥12 months of follow‐up were included. Biopsies were reviewed for the presence of basal plasmacytosis (BPC) and active histological inflammation, defined as a Geboes score (GS) ≥3.2. Primary outcome measures were disease relapse at 18 months and time to first relapse after index colonoscopy. Results: : Seventy‐six UC patients (51% male; mean age, 38.6 years; median follow‐up [range], 75.2 [2‐118] months) were included. Sixty‐two percent had an endoscopic Mayo score of 0 at index colonoscopy. Basal plasmacytosis was present in 46% and active histological inflammation in 30% of subjects. Presence of BPC was associated with a significantly shorter time to disease relapse ( P = 0.01). Active histological inflammation was significantly associated with clinical relapse at 18 months ( P = 0.0005) and shorter time to clinical relapse ( P = 0.0006). Multivariate analysis demonstrated active histological inflammation to be independently associated with clinical relapse at 18 months and time to clinical relapse. Conclusions: : In endoscopically quiescent UC, active histological inflammation and the presence of BPC are adjunctive histological markers associated with increased likelihood of disease relapse. Although prospective studies are required, the presence of these histological markers should be a factor considered when making therapeutic decisions in UC.